Improvements for ZCS-PWM commutation cell in high-power-factor preregulator application - Wakabayashi, F. T.; Canesin, C. A. (Inst Engineering Technology-iet, 2006)
A Summary of different topological arrangements concerning a ZCS-PWM cell is presented, based on the analysis of its application in boost rectifying preregulators, controlled by the technique of instantaneous average values of input current, with the purpose of obtaining high-input-power-factor rectifier and high efficiency in single-phase applications in telecommunication systems. The main characteristics of each switching cell are described, providing conditions to establish a qualitative comparison among the structures. In addition, experimental results are presented for a prototype of the latest version of the ZCS-PWM boost rectifier, implemented for processing normal values of 1200 W output power and 400 V output average voltage, at 220 V Input RMS voltage and 50 kHz switching frequency.